Old forest policy and regulatory frameworks in Nova Scotia and New Brunswick with a comparison to British Columbia - Amy Berry; Amanda Lavers; Lisa Mitchell (The Forestry Chronicle)
Old growth forests (OGF) represent ecological continuity and are rich in biodiversity. These unique landscapes are becoming increasingly rare in Canada, especially within the Acadian Forest Region that covers the Maritime Provinces. Less than 1% of the total forest cover in these provinces is OGF — this is drastically lower than the 55% represented in British Columbia’s Temperate Coastal Rainforest. The authors of this paper conducted a comprehensive comparative analysis of old forest policies and regulatory frameworks in Nova Scotia, New Brunswick and British Columbia to offer recommendations for improving the conservation and stewardship of OGF in the Maritimes. The analysis revealed that in Nova Scotia there is a strong old forest policy underpinned by a quantitative scoresheet, coordinator, and database. In New Brunswick and Nova Scotia the conservation targets are up to 8% on Crown land, but neither have a regulatory framework nor have evidence of achieving these targets. British Columbia has integrated Forest Stewardship Plans that promote the retention of OGF as legally enforceable tools for licensees in Old Growth Forest Management Areas. Such an approach could prove useful in improving the restoration and conservation of OGF in the Maritime Provinces.